THE STUDENTS’ PROBLEM-SOLVING SKILLS IMPROVEMENT BY USING INTEGRATION OF MEANS-ENDS ANALYSIS ON PROBLEM-BASED LEARNING MODEL - YUSRILIA PERMATASARI, NIKMATUS; NISWATI RODLIYATUL JAUHARIYAH, MUKHAYYAROTIN (Inovasi Pendidikan Fisika, 2020)
This research aims to describe the problem-solving skills of students after learning with problem-based learning (PBL) model integrated by a means-ends analysis (MEA) strategy on global warming material content. This type of research is quantitative descriptive, which categorized into the true-experimental design, with a non-equivalent control group design. The subjects in the investigations are students of class XI MNS in the even semester of the 2019/2020 school year of State Senior High School 2 Sidoarjo which includes two experimental classes (XI MNS 1 and XI MNS 2) and one control class (XI MNS 7), whereas the learning model used is PBL model with MEA strategy applied to the "experimental classes" and the learning that commonly involves in school used for the control class. Data collection methods used are test methods and process assessment methods. The results of the pre-test and post-test analyzed by normality test, homogeneity test, paired t-test, One-Way ANOVA, and N-gain analysis. Based on data analysis, the results show that n-gain was in the high category and the improvement in students problem-solving skills in the experimental class is higher than the control class. It implied that the integration of PBL and MEA could implement to another physics material to improve the students problem-solving skills.Keywords: Problem Based Learning (PBL), Means-Ends Analysis (MEA), problem-solving skills